2011
DOI: 10.1074/jbc.m111.235846
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor β (LXRβ) Interacts Directly with ATP-binding Cassette A1 (ABCA1) to Promote High Density Lipoprotein Formation during Acute Cholesterol Accumulation

Abstract: Cells have evolved multiple mechanisms for maintaining cholesterol homeostasis, and, among these, ATP-binding cassette protein A1 (ABCA1)-mediated cholesterol efflux is highly regulated at the transcriptional level through the activity of the nuclear receptor liver X receptor (LXR). Here, we show that in addition to its well defined role in transcription, LXR␤ directly binds to the C-terminal region ( Disruption of cellular cholesterol homeostasis can lead to a variety of pathological conditions, including ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…Unliganded LXRb is exported from the nucleus, whereas unliganded LXRa is retained in the nucleus (Prüfer and Boudreaux, 2007). A recent study has revealed the cytosolic function of LXRs that LXRb directly binds to ABCA1 on the plasma membrane, inhibiting ATP binding to ABCA1 (Hozoji-Inada et al, 2011). Furthermore, cytosolic LXRb directly interacts with activin receptor-like kinase 1 (ALK-1) in the cytoplasm, a type I receptor in the transforming growth factor-b family, leading to the regulation of ALK-1 downstream signaling pathway (Mo et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Unliganded LXRb is exported from the nucleus, whereas unliganded LXRa is retained in the nucleus (Prüfer and Boudreaux, 2007). A recent study has revealed the cytosolic function of LXRs that LXRb directly binds to ABCA1 on the plasma membrane, inhibiting ATP binding to ABCA1 (Hozoji-Inada et al, 2011). Furthermore, cytosolic LXRb directly interacts with activin receptor-like kinase 1 (ALK-1) in the cytoplasm, a type I receptor in the transforming growth factor-b family, leading to the regulation of ALK-1 downstream signaling pathway (Mo et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…19 Second, Hozoji et al described that in THP-1 cells, LXRb is associated with ATP-binding cassette transporter A1 (ABCA1) at the plasma membrane level and that under agonist treatment, LXRb dissociates from ABCA1 to promote cholesterol efflux and translocates to the nucleus to exert its transcriptional activity. 20,21 The cytoplasmic and sub-membrane localization of LXRb could account for its interaction with the intra-cellular C-terminal domain of pannexin 1. Chekeni et al have described that this domain is responsible for the maintaining of the closed conformation of this pore and that the cleavage of this portion by caspase-3 leads to the opening of pannexin 1 and ATP release.…”
Section: Discussionmentioning
confidence: 99%
“…There are also several post-translational regulatory pathways involving calpain-dependent degradation of ABCA1 10 and ubiquitination followed by either proteasomal 11 or lysosomal 12 degradation. Activity and stability of ABCA1 are also regulated by phosphorylation of ABCA1 13 and formation of complexes with ABCA12 14 and LXRβ 15 . Furthermore, ABCA1 is regulated by endocytic recycling between plasma membrane and intracellular compartments, a poorly investigated pathway.…”
Section: Introductionmentioning
confidence: 99%